Get reliable answers to your questions at Westonci.ca, where our knowledgeable community is always ready to help. Our platform provides a seamless experience for finding reliable answers from a network of experienced professionals. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.
Sagot :
To solve the system of simultaneous equations given by:
1. \( x^2 + y^2 = 13 \)
2. \( x = y - 5 \)
we will follow these steps:
Step 1: Substitute the expression for \( x \) from the second equation into the first equation.
Given \( x = y - 5 \), substitute \( x \) in the first equation:
[tex]\[ (y - 5)^2 + y^2 = 13 \][/tex]
Step 2: Expand and simplify the equation.
First, expand \( (y - 5)^2 \):
[tex]\[ (y - 5)^2 = y^2 - 10y + 25 \][/tex]
So the equation becomes:
[tex]\[ y^2 - 10y + 25 + y^2 = 13 \][/tex]
Combine like terms:
[tex]\[ 2y^2 - 10y + 25 = 13 \][/tex]
Step 3: Rearrange the equation into standard quadratic form.
[tex]\[ 2y^2 - 10y + 25 - 13 = 0 \][/tex]
[tex]\[ 2y^2 - 10y + 12 = 0 \][/tex]
Step 4: Simplify the quadratic equation.
Divide every term by 2 to make it easier to solve:
[tex]\[ y^2 - 5y + 6 = 0 \][/tex]
Step 5: Factor the quadratic equation.
[tex]\[ y^2 - 5y + 6 = (y - 2)(y - 3) = 0 \][/tex]
Set each factor to zero to solve for \( y \):
[tex]\[ y - 2 = 0 \quad \text{or} \quad y - 3 = 0 \][/tex]
So,
[tex]\[ y = 2 \quad \text{or} \quad y = 3 \][/tex]
Step 6: Find the corresponding \( x \) values.
Using the second original equation \( x = y - 5 \):
- When \( y = 2 \):
[tex]\[ x = 2 - 5 = -3 \][/tex]
- When \( y = 3 \):
[tex]\[ x = 3 - 5 = -2 \][/tex]
Step 7: Write the solutions as pairs \((x, y)\).
The solutions to the system of equations are:
[tex]\[ (-3, 2) \][/tex]
[tex]\[ (-2, 3) \][/tex]
Thus, the pairs [tex]\((x, y)\)[/tex] that satisfy both equations are [tex]\((-3, 2)\)[/tex] and [tex]\((-2, 3)\)[/tex].
1. \( x^2 + y^2 = 13 \)
2. \( x = y - 5 \)
we will follow these steps:
Step 1: Substitute the expression for \( x \) from the second equation into the first equation.
Given \( x = y - 5 \), substitute \( x \) in the first equation:
[tex]\[ (y - 5)^2 + y^2 = 13 \][/tex]
Step 2: Expand and simplify the equation.
First, expand \( (y - 5)^2 \):
[tex]\[ (y - 5)^2 = y^2 - 10y + 25 \][/tex]
So the equation becomes:
[tex]\[ y^2 - 10y + 25 + y^2 = 13 \][/tex]
Combine like terms:
[tex]\[ 2y^2 - 10y + 25 = 13 \][/tex]
Step 3: Rearrange the equation into standard quadratic form.
[tex]\[ 2y^2 - 10y + 25 - 13 = 0 \][/tex]
[tex]\[ 2y^2 - 10y + 12 = 0 \][/tex]
Step 4: Simplify the quadratic equation.
Divide every term by 2 to make it easier to solve:
[tex]\[ y^2 - 5y + 6 = 0 \][/tex]
Step 5: Factor the quadratic equation.
[tex]\[ y^2 - 5y + 6 = (y - 2)(y - 3) = 0 \][/tex]
Set each factor to zero to solve for \( y \):
[tex]\[ y - 2 = 0 \quad \text{or} \quad y - 3 = 0 \][/tex]
So,
[tex]\[ y = 2 \quad \text{or} \quad y = 3 \][/tex]
Step 6: Find the corresponding \( x \) values.
Using the second original equation \( x = y - 5 \):
- When \( y = 2 \):
[tex]\[ x = 2 - 5 = -3 \][/tex]
- When \( y = 3 \):
[tex]\[ x = 3 - 5 = -2 \][/tex]
Step 7: Write the solutions as pairs \((x, y)\).
The solutions to the system of equations are:
[tex]\[ (-3, 2) \][/tex]
[tex]\[ (-2, 3) \][/tex]
Thus, the pairs [tex]\((x, y)\)[/tex] that satisfy both equations are [tex]\((-3, 2)\)[/tex] and [tex]\((-2, 3)\)[/tex].
Thanks for stopping by. We strive to provide the best answers for all your questions. See you again soon. Thank you for your visit. We're committed to providing you with the best information available. Return anytime for more. Westonci.ca is here to provide the answers you seek. Return often for more expert solutions.